Mapeamento e análise do uso atual da terra no município de areia Pb: Subsídios para o planejamento ambiental - Pereira, Felipy Rafael Marinho (2019)
It is important that the dynamics on the forms of land cover and land use be known, from the organization of the geographic space and from the identification of the most vulnerable areas to the loss of soil as a result of disturbance caused by human activities. Considering this perspective, this work highlights the county of Areia, located in Agreste Paraibano, aiming to provide subsidies for the environmental and economic planning of its managers. In this sense, the research objectives were: I) to diagnose, through the current use of land, the types of use and occupation of the county, as well as the conflicts existing in the APP according to the Forest Law; II) to identify and diagnose the natural vulnerability to soil loss in the county. The database for the development of the work included data from the digital elevation model (MDE) from satellite ALOS/PALSAR, for slope extraction, and SRTM, to obtain drainage density and altimetric amplitude. In addition, it was used the geological maps of leaves SB-25- YA-IV and SB-25-YCI and of soils of Paraíba, the pluviometric data of INMET and the highresolution images of the satellite planetscope for elaboration of the map of land usage and land occupation. The image allowed to identify and to map eleven land use and land cover classes based on image interpretation. Through map algebra it was possible to cross the maps with the objective of integrating the geological, geomorphological, climatic, pedological and land cover characteristics to generate the vulnerability index to soil loss and conflict of use with the environmental legislation. The land usage classes with the smallest mapped areas were reforestation, guava cultivation and citrus cultivation, with 0.05, 0.08 and 0.4 km², respectively. The pasture area is the land use class that has the largest contribution in occupied area, with 161.2 km², corresponding to 59.5% of the county. Analyzing the land use and land cover conflicts in APPs, it was possible to note that land use classes such as pasture, banana and sugar cane cultivation are located in areas that should be legally protected, presenting as inappropriate use. The pasture was the land use class (571.68 ha) that presented the greatest conflict in relation to environmental legislation, corresponding to 52.67% of the APPs being occupied by this class. Eleven land use and land cover classes were identified in the county of Areia-PB, with emphasis on the pasture class, with the highest representativeness. Considering the entire county of Areia, the natural vulnerability to soil loss was classified as 78.7% as moderate, 19.8% as low and 1.5% with high vulnerability. Thus, it was verified that the degree of natural vulnerability to soil loss was concentrated in the moderate class, being possible to observe that the themes land use and pedology were the ones that had the most influence in this aspect. The study of the natural vulnerability to soil loss of the county is of fundamental importance for the environmental planning, since it allowed to analyze the potentialities and the limitations of the county regarding the environmental factors worked, in addition to identifying which environmental factors most contribute to the environmental degradation.